Artificial Intelligence in Civil Engineering: A Comprehensive Review on Smart Infrastructure, Urban Planning, and Sustainable Development (International Journal of Food and Nutritional Sciences, 2021)
When artificial intelligence (AI) is used in civil engineering, it changes the future of infrastructure, urban environments, and sustainable growth. Robotics, computer vision, neural networks, and predictive analytics are some examples of artificial intelligence (AI) technologies that could change many important areas of civil engineering. AI makes smart infrastructure better in three ways: it can automatically check the health of buildings, handle construction projects smartly, and plan maintenance ahead of time. Tools for optimising traffic, GIS-based models, and AI-driven simulations in urban planning are helping to make cities that are strong, efficient, and liveable. how AI can improve the use of materials, save energy, and help with environmentally friendly designs, all of which are important for long-term growth. The review brings together the newest ideas, useful applications, and important scholarly advances by using case studies and cross-disciplinary research from both developed and developing countries. Using AI in civil engineering education, policy, and practice is important to encourage new ideas and make sure that the built world will last for a long time. However, there are persistent problems that need to be fixed. These include data protection, algorithmic bias, high implementation costs, and the need for people from different fields to work together. Still, the pros of using AI must also be thought about.